Characteristics of electronic cigarette user and traditional smokers: 2017 Youth risk behavior surveillance system. Issue 6 (8th June 2021) - Lee, Young‐Shin; Yang, Kyeongra; Kameg, Brayden; Palmer, Josh; Lee, Heeyoung
Abstract: Background: Although electronic cigarette (e‐cigarette) use among adolescents rapidly has increased over the past decade, which has raised concerns over the corresponding behavioral health risks, the current literature presents limited data for understanding the characteristics of adolescent e‐cigarette users. Objective: The purpose of this study was to (1) identify general characteristics that may be shared between e‐cigarette users and traditional cigarette smokers and (2) examine the unique characteristics of e‐cigarette users vis‐à‐vis traditional cigarette smokers. Design: Cross‐sectional descriptive study. Sample and data source: A total of 14, 765 9th‐ to 12‐grade students drawn from the CDC 2017 Youth Risk Behavior Surveillance System. Results: We observed that the prevalence of marijuana, alcohol, and other illicit drug use was higher among e‐cigarette users and traditional tobacco users than non‐users. Moreover, physically active adolescents were more likely to use e‐cigarettes than those who were physically inactive, although the level of the activity did not predict smoking status. Conclusion: We recommend that primary prevention strategies for e‐cigarette use should be incorporated in physical education programs and target adolescents who engage in not only health risk behaviors, but also health promoting behaviors, such as physical activity.